Pengaruh Peran Lingkungan Sekolah Peran Lingkungan Keluarga Dan Peran Lngkungan Bermain Terhadap Minat Belajar Siswa Di Sman 3 Dumai - Tri Warisya (Institute Agama Islam Tafaqquh Fiddin Dumai, 2022)
The role of the school environment, the role of the family environment and the role of the environment play a very influential role in the world of education. This is an event to make a comparison for schools, families, and students in education. what if the rules that are applied are implemented in the school environment as well as in the family environment and in the play environment then interest in learning will also be good. This study aims to determine the effect of the role of the school environment, the role of the family environment and the role of the environment in learning interest in SMA Negeri 3Dumai. The data used in this study were perimer data obtained through a questionnaire on 78 students. This research is a population study. The data were analyzed using multiple linear regression analysis, with the help of the software spss-21 for window. The results showed that together the role of the family environment and the role of the environment in play had a significant effect on learning interest in SMA Negeri 3Dumai. The regression mode Y = 43.754 + 0.049 (X1) + 0.512 (X2) + 0.412 (X3). The relationship between the role of the school environment, the role of the family environment and the role of